Appearance anxiety and social anxiety: A mediated model of self-compassion - Jie Gao; Jie Gao; Yi Feng; Yi Feng; Shicun Xu; Shicun Xu; Shicun Xu; Amanda Wilson; Hui Li; Xiaofeng Wang; Xi Sun; Yuanyuan Wang; et al. (Frontiers Media S.A., 2023)
BackgroundPrevious studies have focused on the comorbidity of appearance anxiety and social anxiety, but few studies have focused on the protective role of self-compassion as underlying this mechanism, in young people like University students. With the increase of prevalence of appearance anxiety and social anxiety in this age group, it is necessary to explore factors that can buffer against the symptoms of these disorders. Therefore, the aims of this study were to research the effect of appearance anxiety and social anxiety, then to examine whether self-compassion has a protective effect on social anxiety.MethodThe study was cross-sectional and conducted online from October 2021 to November 2021 in Jilin Province, China. A total of 63 Universities in the province participated in this study, totaling 96,218 participants, of which 40,065 were males (41.64%) and 56,153 females (58.36%), the mean age of the sample was 19.59 (±1.74). The Appearance Anxiety Scale-Brief Version was used to measure appearance anxiety. The Social Anxiety subscale of the Self-Consciousness Scale was used to measure social anxiety. The Self-Compassion Scale-Short Form was used to measure self-compassion. A structural equation model (SEM) was run to examine the mediating effect of self-compassion on the relationship between appearance anxiety and social anxiety.ResultOverall, appearance anxiety was positively associated with social anxiety [β = 0.334, 95% CI = (0.328, 0.341), p < 0.001], and self-compassion could mediate the effect of appearance anxiety on social anxiety [β = 0.128, 95% CI = (0.124, 0.132), p < 0.001]. Self-compassion played a partial mediating role between appearance anxiety and social anxiety.ConclusionIndividuals with high appearance anxiety are also at higher risk of social anxiety, but self-compassion can buffer against this relationship. These findings begin to explore novel approaches to treat social anxiety and can provide valuable insights for self-compassion training.